Análisis y diseño de una red de distribución de contenido para el fortalecimiento del servicio de comunicación de la Universidad Técnica de Babahoyo - Prieto Solano, Cristina Alexandra (2021)
Through this research, the experience acquired in the analysis and design of a content distribution network is presented, implementing strategies that help to strengthen the communications service of the Technical University of Babahoyo; For this purpose, CDN systems are the most common techniques used for distribution and live transmission, each with its own set of advantages and disadvantages, for this reason CDN inherits the best of both worlds (Digital and Analogue) as well as the quality control and the reliability of information and the inherent scalability of a communications system. It is possible to address several key challenges in the design and possibility of implementing the system, which include the dynamic scaling of resources in real time that in turn guarantees the quality of the flow, even if it is a low startup latency, and therefore facilitates the integration of the existing infrastructure providing compatibility with the network with equity in the operation of interconnectivity between end users and the CDN network; in the same way, it is possible to evaluate the performance using data from this implementation of the real world in a controlled environment for a correct deployment of coverage in the UTB with a compendium of digital content